Myocardial infarction in young adults risk factors And pattern of coronary artery involvement - إياس الخير , (Latakia University Journal -Medical Sciences Series, 2023)
Background Coronary artery disease (CAD) mostly occurs in persons older than 45 years of age. In India, CAD manifests almost a decade earlier than in Western countries. This study was done to study the risk factors and angiographic profile in young patients presenting with acute myocardial infarction (AMI). Patients and Methods: One hundred and twenty-four consecutive patients presenting with AMI at less than 40 years of age were studied for risk factors. Coronary angiography was done in all. Results: Out of 124 patients, 123 were male. Mean age was 35.94 yrs. One hundred and eighteen had ST elevation myocardial infarction (MI) (95.16%) and six had non ST elevation MI (5.84%). Anterior wall MI was present in 88 patients (70.97%), inferior wall MI in 31 patients (25%) and lateral wall MI in five patients (4.03%). Seventy-three patients (58.8%) were smoker, 55 were hypertensive (44.35%), 10 were diabetic (8.06%). Family history of CAD was present in 22 (17.7%) patients. Low High‑density lipoprotein (HDL) was seen in 53 patients (42.7%), and high triglycerides in 60 patients (48.38%). Significant CAD was found in 88 (70.96%) patients, 13 (10.48%) had normal coronaries. Single vessel disease was seen in 57 patients, two‑vessel disease in 15 patients and three‑vessel disease in eight patients. Total 125 lesions were seen and left anterior descending (LAD) was the commonest vessel involved, with 78 lesions (62.4%). Conclusion: AMI in young almost exclusively occurs in male, and ST elevation MI is the main presentation. Anterior wall MI is most common, with LAD being involved in around 2/3 patients. Smoking, hypertension, low HDL and high triglycerides are the major risk factors.